Weather uncertainty and demand for information in technology adoption: Case of Namibia - Visser, M.; Mulwa, C.K.; Gitonga, Z.; Baard, M. (Elsevier, 2025)
This study examines the impact of risk and ambiguity preferences on farmers' technology adoption decisions under uncertainty, with an emphasis on the role of precise weather information in guiding these decisions. Using framed lab-in-the-field experiments conducted with rural households in the North-Central region of Namibia, we elicit individual risk and ambiguity attitudes and observe technology choices across varying levels of known and unknown probabilities of favourable weather. Our findings show that risk-seeking behaviour significantly increases the likelihood of adopting higher-risk, higher-return agricultural technologies when probabilities are known. Under ambiguity, both risk and ambiguity preferences significantly influence technology choices, with ambiguity-averse farmers tending towards safer options. Importantly, we demonstrate that farmers' willingness to pay for precise weather information escalates with the level of objective uncertainty that they face. Access to accurate weather forecasts leads to significant improvements in weather-related decisions under complete uncertainty, promoting the adoption of improved technologies and increasing expected payoffs. These results underscore the crucial role of objective uncertainty in shaping demand for information and highlight the potential of targeted weather information services to enhance farmers' agricultural decision-making, particularly in the arid and semi-arid regions of sub-Saharan Africa. Our study contributes to the literature by providing empirical evidence on how reducing uncertainty through information provision can facilitate technology adoption, suggesting that investments in weather forecasting and dissemination could substantially benefit farmers in regions vulnerable to climate variability and when there are high levels of objective uncertainty.